Representation of Hope and Optimism in RedOne’s Song “La Mustahila”: The Diction, Linguistic Styles, and Implied Meanings - Mohammad Rofiqi; Ibnu Burdah; Moh. Habib (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the lyrics of the song “La Mustahila” by RedOne from stylistic and semantic perspectives, considering it as a literary text that possesses aesthetic and expressive value. Language in song lyrics is not merely a means of communication, but also serves as an artistic medium rich in meanings and implicit connotations. This research employed a descriptive qualitative method using documentation techniques and data analysis based on the Miles and Huberman model, while also drawing on Gorys Keraf’s stylistic theory and Geoffrey Leech’s semantic theory. The results of the study indicate that the song lyrics demonstrate significant stylistic richness, particularly in sentence structure, such as repetition, parallelism, antithesis, and gradation (climax). In addition, several rhetorical styles were identified, including imperative expressions, hyperbole, ellipsis, and inversion, all of which strengthen the motivational and persuasive nature of the text. From a semantic perspective, the song contains various types of meaning, including conceptual, connotative, affective, social, and collocative meanings, which work together to convey messages of optimism and belief that nothing is impossible. Keywords: “La Mustahila” song lyrics, stylistic theory, semantic theory, optimism, hope.